2014
DOI: 10.1159/000363683
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Hair Cells in Sensorineural Hearing Loss

Abstract: Purpose: Since the completion of the human genome project, the exploration of the molecular basis of sensorineural hearing loss has been an area of intensive research. In this review, we attempt to summarize the knowledge on genes or proteins in hair cells related to sensorineural hearing loss. Investigating expression and function of these genes will help us to understand the molecular mechanisms of deafness. Findings: There are about 70-100 genetic loci which are related to deafness. Some of them are signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Inner hair cells (IHCs), the actual sensory receptors, play a crucial role in the conversion of mechanical movements to electric signals. 8 -14 Hearing ability relies on the rapid gating of the mechanoelectrical transduction (MET) channels believed to be located in the tip of the hair cell stereocilia (Figure 2A). 15,16 The genes encoding the MET channel have not yet been identified.…”
Section: Resultsmentioning
confidence: 99%
“…Inner hair cells (IHCs), the actual sensory receptors, play a crucial role in the conversion of mechanical movements to electric signals. 8 -14 Hearing ability relies on the rapid gating of the mechanoelectrical transduction (MET) channels believed to be located in the tip of the hair cell stereocilia (Figure 2A). 15,16 The genes encoding the MET channel have not yet been identified.…”
Section: Resultsmentioning
confidence: 99%
“…Sensorineural hearing loss (SHL) is defined as the damage, degeneration, or loss of the cochlear hair cells (HCs) [12,13] or spiral ganglion neurons [14][15][16] in the auditory system. The majority of SHL patients are diagnosed with congenital SHL including syndromic and non-syndromic SHL.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a total of 70-100 genetic loci are associated with SHL. These genetic loci are usually found in genes responsible for signal transduction, membrane ion channel expression, HC development, and aging processes [13]. Most of the genes are directly related to the function of the outer HCs in fine-tuning incoming sound waves.…”
Section: Introductionmentioning
confidence: 99%